1972
DOI: 10.1073/pnas.69.6.1634
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Bacteriophage M 13: Inhibition of Single-Strand DNA Synthesis by Rifampicin

Abstract: Synthesis of single-stranded DNA of bacteriophage M 13 is blocked by rifampicin. This inhibition is not observed in an Escherichia coli mutant possessing an RNA polymerase resistant to rifampicin. Since rifampicin stops single-strand synthesis faster than chloramphenicol, inhibition by rifampicin does not seem to result from a transcriptional block of protein synthesis, particularly in view of the long half-life of the messenger RNA for M 13. It is, therefore, concluded that the interaction of rifampicin with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 15 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that rif'ampin, an inhibitor of ribonucleic acid (RNA) polymerase, blocks the conversion of M13 single-strand DNA to the replicative form (2,35,38,39), but fails to block the synthesis of' X174 replicative form (38). It has been f'urther reported that a transcriptional step is directly involved in DNA replication of' various replicons: phage X (7,15,32), T7 (10), colEl (3,4,30,31), F (17,18), R64-11 (8), plasmid of E. coli 15 (22), plasmid of' Salmonella pullorum ( 16), E. coli (12, 13, 19, 21; T. Saitoh and S. Hiraga, accepted for publication), and Bacillus subtilis (20,23).…”
mentioning
confidence: 99%
“…It has been reported that rif'ampin, an inhibitor of ribonucleic acid (RNA) polymerase, blocks the conversion of M13 single-strand DNA to the replicative form (2,35,38,39), but fails to block the synthesis of' X174 replicative form (38). It has been f'urther reported that a transcriptional step is directly involved in DNA replication of' various replicons: phage X (7,15,32), T7 (10), colEl (3,4,30,31), F (17,18), R64-11 (8), plasmid of E. coli 15 (22), plasmid of' Salmonella pullorum ( 16), E. coli (12, 13, 19, 21; T. Saitoh and S. Hiraga, accepted for publication), and Bacillus subtilis (20,23).…”
mentioning
confidence: 99%
“…Whereas inhibition of protein synthesis by chloramphenicol (CAP) blocks the replication of chromosomal DNA and DNA of transmissible plasmids (2), de novo protein on October 9, 2020 by guest http://jb.asm.org/ Downloaded from VELTKAMP, BARENDSEN, AND NIJKAMP synthesis appeared not to be required for the replication of the non-transmissible plasmid Col El (6), minicircular DNA of E. coli 15 (27), or Clo DF13 (this report). RNA synthesis is a prerequisite for the replication of chromosomal DNA and for DNA of transmissible as well as non-transmissible plasmids (3,5,7,8,12,20,24,26,27,33,35). It has been shown that rifampinsensitive RNA synthesis is required for the initiation of chromosomal DNA replication at the fixed origin (26).…”
mentioning
confidence: 99%